2020
DOI: 10.1016/j.foreco.2019.117682
|View full text |Cite
|
Sign up to set email alerts
|

The effects of thinning management on bats and their insect prey in temperate broadleaved woodland

Abstract: Trees, woods, forests and associated biodiversity are being affected by anthropogenic climate breakdown, and need management to maintain delivery of a wide range of ecosystem services. Wood harvested from sustainably managed woodlands can be used to mitigate greenhouse gas emissions through carbon substitution, directly using biomass for bioenergy to replace fossil fuels or indirectly through the use of wood products instead of higher carbon footprint materials such as concrete and steel. However, it is also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Free space within forest gaps, which is restricted in size and differs space in gaps at mid and high heights probably offered highly profitable occurrences in lepidopteran prey (Rydell et al, 1996;Sierro & Arlettaz, 1997). Burford et al (1999) and Carr et al (2020), however, found moth species richness, occurrence, and abundance to be positively related to vegetation clutter, but Barbastelle bats-as large and rather fast flying ESFs-are precluded from cluttered vegetation. In the forest interior, their activity was four times lower compared to canopy gaps and restricted to the lower two layers where limited hunting possibilities were available.…”
Section: Mb M Ramentioning
confidence: 99%
“…Free space within forest gaps, which is restricted in size and differs space in gaps at mid and high heights probably offered highly profitable occurrences in lepidopteran prey (Rydell et al, 1996;Sierro & Arlettaz, 1997). Burford et al (1999) and Carr et al (2020), however, found moth species richness, occurrence, and abundance to be positively related to vegetation clutter, but Barbastelle bats-as large and rather fast flying ESFs-are precluded from cluttered vegetation. In the forest interior, their activity was four times lower compared to canopy gaps and restricted to the lower two layers where limited hunting possibilities were available.…”
Section: Mb M Ramentioning
confidence: 99%
“…As expected, P. kuhlii/nathusii, and P. pygmaeus / M. schreibersii were negatively affected by vegetation clutter. These edge-specialist foragers are known to avoid foraging or commuting in highly cluttered situations 6 , 9 , 12 , 37 . Stands with open canopy and low shrub cover may therefore represent optimal foraging habitats for these species.…”
Section: Discussionmentioning
confidence: 99%
“…There is strong support for bat activity in forest ecosystems being more related to habitat structure than to prey abundance 37 , 38 , 51 , 52 . Yet, the interactive effect between prey abundance and habitat structure has been largely overlooked to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies generally recommend preserving old‐growth stands or retaining mature trees and snags in mixed‐age stands since many tree‐roosting bats appear reliant on these habitats (e.g., Burgar et al., 2015 ; Perry & Thill, 2007 ; Webala et al., 2010 ). Thinning trees or clearing understory foliage to promote the growth of remaining trees may benefit open‐space and edge‐foraging bats while negatively impacting clutter‐foraging species (e.g., Patriquin & Barclay, 2003 , Carr et al., 2020 ). For example, species including the open‐space foraging Lasiurus seminolus prefer roosting in relatively open forests (Perry et al., 2007 ), while the clutter‐foraging Barbastella barbastellus prefer roosts in unmanaged forests with dense understory (Russo et al., 2004 ).…”
Section: Introductionmentioning
confidence: 99%